Própolis de abelha nativa sem ferrão da espécie Frieseomelitta varia: determinação da composição química e atividades biológicas - Hipólito, Taciane Maíra Magalhães (2013)
The therapeutic aid exercised by propolis of honeybee Apis mellifera is known since immemorial times and their properties have been widely studied. However, the stingless bee propolis has been little investigated. In this way, this work proposed to assess some chemical characteristics and biological activities of propolis produced by Frieseomelitta varia stingless bees. The samples (Fv1, Fv2 and FvA) were obtained in different times and places in the city of Alfenas-MG. Extraction were made with them in ethanol and the resultant extracts were submitted to some evaluations: UV-visible absorption profile, composition by flavonoids (quercetin), phenolic compounds (based on Gallic acid) and chemical profile by thin-layer chromatography (TLC). Additionally, Fv1 Fv2 and FvA were examined by in vitro biological assays, such as antimicrobial, antioxidant and antiproliferative activities. The absorption spectrum of UV-visible light showed characteristic peaks of phenolic compounds and flavonoids, on the other hand, the quantitative tests showed low values of these phytochemicals. The TLC result revealed the presence of terpenoides in all the samples. With regard to biological properties, low antioxidant activity was found. However, the antimicrobial and antiproliferative results, were quite relevant. The sample Fv1 showed ability to inhibit fully the growth of ovarian cancer cells resistant to drugs at a concentration of 7.6µg/mL, below the required value of the standard Doxorubicin to inhibit this same cell line. In the antimicrobial assays, Fv1 also stood out for its bactericidal action on Streptococcus agalactiae in concentration contained between 15.62 -31.25µg/mL, also lower than the value obtained with the standard Chloramphenicol. The results found in this research show the great biological properties of Frieseomelitta varia propolis, which can change according to location and time of collection.